Sharing the positive or the negative? Understanding the contect, motivation and consequence of emotional disclosure on Facebook - Lin, Han (2014)
The recent emergence of Social Networking Sites (SNSs), such as Facebook, provides substantial opportunities for emotional disclosure. A relevant and timely question arises concerning how such a context alters as well as supports emotional disclosure. Three studies were conducted to address this issue. Study 1 compares individuals’ emotional disclosure in the context of Facebook versus diary writing and real life. Results show that emotional disclosure on Facebook is more frequent than in diaries, but less frequent than in real life, supporting the notion that emotional disclosure is determined by the sociality of the context. Using a social network analysis, Study 2 further tests how emotional disclosure is associated with social network properties—network size and density. It further demonstrates that network size is associated with disclosure of positive emotions because of need for impression management, while network density is associated with both disclosure of positive emotions and disclosure of negative emotions through the need for emotional expression. Study 3 extends the concerns to the influence of emotional disclosure on well-being. Results reveal that emotional disclosure is related to fulfillment of both needs. Fulfillment of need for impression management accounts for the positive association between positive emotional disclosure and well-being, whereas fulfillment of neither need mediates the negative association between negative emotional disclosure and well-being. The set of studies demonstrates how the motivational needs play roles in the associations between emotional disclosure, context, and well-being. Altogether, this research offers a compelling account of emotional disclosure in a complicated social context and sheds light on leveraging SNSs for well-being.